PENGARUH KONDISI SOSIAL EKONOMI ORANG TUA TERHADAP TINGKAT PENDIDIKAN ANAK KELUARGA NELAYAN DI DESA PUGER-KABUPATEN JEMBER - I Wayan Wenagama, Andre Santoso, (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
This study aims to determine the effect of parents' education level, age, income, and number of responses on children's education levels simultaneously and partially, as well as knowing the most dominant variables affecting the level of children's education. The results of the simultaneous analysis of F arithmetic (4,397)> from the F table (2.54) indicate the level of education of parents, age, income, number of dependents simultaneously have a significant effect on the level of children's education. Coefficient determination compound value of 0.242 that the level of education of children is influenced by the level of education of parents, age, income, number of dependents by 24.2% and the remaining 75.8% is influenced by other factors. Age and number of dependents significantly influence the level of education of children, while the level of parental education and income partially do not affect the level of education of children. T test results show that the variable t count age (2,220), and the number of respondents (2,029) is greater than t table (1,672), while the variable level of parent education (-1,658) and income (-3,178) is smaller than t table (1,672) ). The age variable and number of dependents had the most dominant influence on the level of children's education in Puger Village, Jember Regency, East Java.